Parenting Strategies for Building Responsible Character in Orphans - Pitri Iraya Nasution; Muhammad Basri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character education is crucial in shaping children’s personalities, with responsibility being a core value for social and personal development. This is particularly significant for orphans, who often face emotional vulnerabilities due to parental loss and require structured guidance in institutional care settings. Specific Background: The Annur Orphanage in Medan implements various parenting strategies aimed at fostering responsibility among its residents. However, previous studies on orphanage-based character formation have been limited, often lacking focus on specific traits like responsibility. Knowledge Gap: Few studies examine in detail the systematic parenting strategies within orphanages, especially in Annur Orphanage, and their role in cultivating responsibility in children. Aims: This study aims to explore and analyze the parenting strategies employed at Annur Orphanage to instill a sense of responsibility in orphans. Results: Using a descriptive qualitative approach, findings reveal that caregivers apply habituation, exemplary modeling, and task assignments—integrated with religious and moral values—supported by structured routines and compassionate engagement. These methods have proven effective in building independence, discipline, and social responsibility, despite challenges like limited resources and varied child backgrounds. Novelty: This research provides a focused, in-depth analysis of responsibility-oriented parenting strategies in an orphanage context, offering practical implications for similar institutions. Implications: The results can inform policy and practice in child welfare organizations, highlighting the importance of consistent, value-based, and humanistic approaches to developing responsible character in vulnerable children. Highlights: Effective use of habituation, example, and task assignment. Integration of religious and moral values in daily routines. Humanistic approach despite resource limitations. Keywords: Parenting Strategies, Responsible Character, Orphans, Annur Orphanage, Character Education